If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+5x=3(5-2x)+2
We move all terms to the left:
3x+5x-(3(5-2x)+2)=0
We add all the numbers together, and all the variables
3x+5x-(3(-2x+5)+2)=0
We add all the numbers together, and all the variables
8x-(3(-2x+5)+2)=0
We calculate terms in parentheses: -(3(-2x+5)+2), so:We get rid of parentheses
3(-2x+5)+2
We multiply parentheses
-6x+15+2
We add all the numbers together, and all the variables
-6x+17
Back to the equation:
-(-6x+17)
8x+6x-17=0
We add all the numbers together, and all the variables
14x-17=0
We move all terms containing x to the left, all other terms to the right
14x=17
x=17/14
x=1+3/14
| 3x∘=2x∘+50∘ | | 4x-2=4(x-1)+9 | | 6m+9=63m= | | x+x/2+x/3+4=26 | | 9h-25=65h= | | a÷3+3=16a= | | 7m-11=52m= | | n2=3n-30 | | 6m+7=25m= | | 4z/9+8=7z= | | 45+4x+x=180 | | 25y+1=56y= | | 5s-12=13 | | x/9+5=1x= | | 2x-(-10)=30 | | 4y−6=2y | | (x+42)∘+3x∘=90∘ | | 2x^2+1=x+2x^2 | | 8h+6=62h= | | t÷5-8=10t= | | a÷6+2=10a= | | 3x=-4x-2/5 | | 5^2x-1=12 | | 57-4x=13x+16 | | 3x+15=60° | | 3(2x-3)=-5x | | 2p-6=8-5(p+9) | | 1/9c=21 | | 2x+1/2+3x-2/3=2x-1/3+3x+1/2 | | 3x-12+2=2x+10 | | 5x=80/2 | | 3x-2x=12-2+10 |